ECG Quiz no. 17 - Okreglicki, A (SA Heart Journal, 2017)
This is the ECG of a 38 year-old woman who has been referred for the fi rst time to the cardiac clinic for evaluation. She has a long history of effort related dyspnoea that has recently become much worse.